Assessing Data Center Infrastructure Readiness Through Energy, Reliability, and Scalability Metrics - Ahmed Al-Mansouri (Kalam Practica Media, 2026)
Data centers have become critical infrastructure for digital services, yet their expansion increases pressure on electricity systems, cooling capacity, system resilience, and service scalability. Infrastructure readiness cannot be assessed only through facility availability or energy efficiency because digital service continuity depends on the interaction between power use, thermal stability, redundancy, and workload growth capacity. This study developed and tested a quantitative experimental readiness assessment model for data center infrastructure based on energy efficiency, system reliability, and digital service scalability. A simulated experimental dataset representing 30 operational scenarios was generated from a medium-scale data center configuration with five workload levels, three cooling setpoint strategies, and two redundancy configurations. Energy efficiency was measured using Power Usage Effectiveness, cooling load ratio, and server utilization. Reliability was measured using modeled availability, mean time between failure, mean time to repair, and thermal incident frequency. Scalability was measured using workload absorption capacity, latency stability, and resource headroom. A composite Data Center Infrastructure Readiness Index was calculated using normalized weighted scores. The optimized configuration produced the highest readiness score of 84.72 out of 100, with mean Power Usage Effectiveness of 1.42, modeled availability of 99.982%, and workload absorption capacity of 81.30%. The baseline configuration scored 68.45, while the constrained configuration scored 57.18. One-way analysis of variance indicated statistically significant differences among configurations for readiness score, energy efficiency, and scalability indicators. The proposed model offers a replicable engineering approach for assessing data center readiness before facility expansion, workload migration, or digital service scaling.